Muscle relaxation and sports - Kato, K.; Kanosue, K. (Sports Performance, 2015)
Muscle relaxation is important in both daily life and sports. In addition, movement disorders such as Parkinson`s disease and Dystonia are often characterized by deficits of muscle relaxation. Activation of some brain areas has been demonstrated during muscle relaxation, suggesting that muscle relaxation might be an "active process", and not just the end of contraction. In the sports field, beginners or players under stress often find relaxation of particular muscles is difficult. However, the mechanisms underlying muscle relaxation during sports is not well understood.